Human resources in the ICU: adaptation of a standard model for Colombia based on the scientific evidence (2015)
Introduction The number of intensive care units (ICU) in Colombia has increased in the last 25 years and its magnitude is not well known. In contrast, trained human resources are scarce, and postgraduate higher education programs have been available for less than 15 years. The distribution and number of graduated practitioners needs to be known. Materials and method A literature search was performed looking for studies on human resources in ICU and their association with primary and secondary outcomes. The Colombian regulations were also reviewed. Results One hundred and twenty national and international articles were found. Colombian regulations from 1990 to date were reviewed. Descriptive, analytical or experimental studies in English or Spanish were included. Discussion and conclusions There are a significant number of adult, pediatric and neonatal ICU beds in Colombia. Nevertheless, there is an insufficient number of critical care trained practitioners, which make them scarce where they are needed. The evidence broadly shows better outcomes when critical care patients are treated by the best-trained human resources. This lack of planning and control in the sector generates an unfair distribution, not necessarily based on the actual needs. A bigger problem is the lack of standardization of this need (load of work) and the quality of human talent in the upgrades of the rulings and by the scientific associations. A greater effort is required between universities, associations and health ministry to promote coverage of these vacancies with suitable and ideal staff, and to establish timely referral strategies for remote sites so that patients may receive a better care.